Lessons and Challenges of Social Work Practice: Reflections from Managing Complex HIV/AIDS Cases in Uganda (Journal of Comparative Social Work, 2008)
This article explores the complexities of working as a social worker with people who have HIV/AIDS in Uganda. The exploration takes the form of a detailed case study.